'Neutral' Representations of Pacific Islands in the IPCC Special Report of 1.5°C Global Warming. Issue 1 (2nd January 2022) - Germano, Maia
ABSTRACT: Pacific Islands are facing some of the most immediate and direct impacts of climate change. The Intergovernmental Panel on Climate Change (IPCC) Special Report of 1.5°C Global Warming (SR15) outlines the possibility that some low-lying atolls will become uninhabitable by 2030 and submerged by 2100. I analyse how and where SR15 presents climate change impacts for Pacific Islands. In doing so, I seek to highlight to what extent the IPCC's structures and pressures influence SR15's marginalisation of or emphasis on Pacific perspectives and challenges. The main findings that emerge from this discourse analysis are, first, that climate change impacts for Pacific Islands are largely conceptualised as relating to the physical environment and the economy. Second, SR15 frames Pacific Islands as vulnerable; however, it appears to be reflecting a shift in the literature toward recognising Pacific adaptation and resilience. The third finding is that the IPCC explicitly defines and acknowledges Indigenous and local knowledge but frames this knowledge as alternative to scientific expertise. I interpret these findings in the context of the underrepresentation of Pacific authors, the availability of published knowledge for assessment and the IPCC's claims of neutrality. Pacific leaders and communities continue to advocate for the 1.5°C threshold investigated in SR15 and are mobilising IPCC assessments.